(untitled) (Research, Society and Development, 2020)
Additive manufacturing is growing rapidly in the automotive, medical, and aerospace industries as an option for the manufacturing of products. However, there is a continuous growth in the amount of waste generated by 3D filaments, thus, the reuse practice becomes important, since it brings environmental and economic gains. The present research evaluated the mechanical, thermal, thermomechanical and rheological properties of PLA/PLAr blends containing post-consumption 3D filament. The blends were prepared in a co-rotational twin screw extruder and, subsequently, the extruded granules were injection molded. As the PLAr content in the blends (PLA/PLAr) increased, there was a reduction in viscosity, indicating an improvement in manufacturability. The PLA/PLAr blend (75/25 % wt.) increased the degree of crystallinity compared to neat PLA, indicating that PLAr acted as a nucleating agent. As a consequence, the PLA/PLAr blend (75/25 % wt.) showed performance comparable to neat PLA in thermal stability, elastic modulus, tensile strength, Shore D hardness, impact strength, heat deflection temperature (HDT) and Vicat softening temperature. The reuse of post-consumption 3D filament PLA is feasible for the development of materials with good properties. In addition, value is added to the post-consumption material and there is a contribution to sustainable development.